Approximation Properties of Durrmeyer Type of (p,q)-Bleimann, Butzer, and Hahn Operators - Qing-Bo Cai; İsmet Yüksel; Ülkü Dinlemez Kantar; Bayram Çekim (Journal of Function Spaces)
In this study, we introduce a Durrmeyer type of Bleimann, Butzer, and Hahn operators (BBH) on (p,q)-integers. We derive the some approximation properties for these operators. We also give some graphs and numerical examples to illustrate the convergence properties of these operators to certain functions.